A SIMULTANEOUS EQUATION MODEL OF GLOBALIZATION, CORRUPTION, DEMOCRACY, HUMAN DEVELOPMENT AND SOCIAL PROGRESS - Mishra, Sudhanshu (The European Journal of Applied Economics, 2018)
This study builds a simultaneous equation model that establishes interconnectionsamong the measures of globalization, measures of democracy,human development, corruption perception index and per capita income,which in turn jointly influence social progress. The model has elevenequations in which the response variables and the predictor variablesare log-linearly related. The empirical data used for estimation of themodel pertain to the period 2006-2016 for 116 countries distributed overall the continents. The model has been estimated by the conventionalTwo-Stage Least Squares (2-SLS) and alternatively by a modified 2-SLSin which, at the second stage, Shapley value regression has been used toameliorate the detrimental effects of collinearity among the predictorvariables. The modified 2-SLS outperforms the conventional 2-SLS. Thestudy finds that globalization positively influences and is influencedby democracy, human development and social capital. Globalizationreduces corrupt practices and integrity promotes globalization. Democracy,social capital, human development and globalization affect socialprogress positively. It has also been found that trans-border personalconnection, cultural proximity, democracy and social capital are elasticwith respect to their predictors.